Knowledge, Attitude and Practice of Mothers with regard to the Warning Signs of Respiratory Infections and Diarrhea in Children below the Age of Five in Arak in 2014 - Tahereh Razi; Mohsen Shamsi*; Nasrin Roozbehani; Mehdi Ranjbaran; Mahbobeh Khorsandi (Journal of Education and Community Health)
Background and Objectives: The majority of children's diseases have certain symptoms and warning signs. The mothers' knowledge of the signs and symptoms of these diseases, particularly of respiratory and gastrointestinal diseases, helps reduce mortality rates in children under the age of five. The present study was conducted to determine the knowledge, attitude and practice of mothers with respect to the warning signs of diseases in children less than the age of five. Materials and Methods: The present descriptive-analytical study was conducted on 350 women with children under the age of five admitted to the healthcare centers of Arak and selected through random sampling. The study's data collection tool was a questionnaire consisting of different parts on the patients' demographic details, knowledge, attitude and practice. The validity and reliability of the questionnaire were confirmed before beginning the study. Data were collected through interviews and then analyzed in SPSS-19 using the independent t-test, the Pearson correlation test and the one-way ANOVA. Results: The mean score ± standard deviation was 60.71±13.7 for knowledge about the warning signs, 77.45± 5.29 for attitude and 49.5±41.5 for practices aimed at respiratory infections, 49.25±41.42 at diarrhea and 52.1±42.91 at febrile seizure. There was a significant difference between the working mothers and the housewives in terms of practice. The mothers' practices differed significantly with their economic status and level of education. Attitude had a significant positive relationship with knowledge and practice (P<0.001). Conclusion: The findings of the present study can be helpful in the design and implementation of educational programs for promoting mothers' knowledge, attitude and practice with regard to the warning signs of diseases in their children.